The Meaning of Muhammadiyah Organizational Communication Networks in the Film Buya Hamka Vol. 1: Roland Barthes' Semiotic Analysis of the Representation of Leadership and Da'wah Authority - Muhammad Randicha Hamandia; Anang Anas Azhar (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2026)
The film Buya Hamka Vol. 1 (2023) is a cultural artifact that visually represents the dynamics of Islamic broadcasting and the manifestation of print communication technology in early 20th-century Indonesia. This study aims to examine the meaning of the Muhammadiyah organizational communication network, the representation of leadership, and the da'wah authority of Buya Hamka using Roland Barthes' semiotic analysis approach. By dissecting the signification of denotation, connotation, and myth in key scenes and dialogues, this research reveals that the Muhammadiyah organizational communication network did not operate in a vacuum, but was closely intertwined with political communication strategies under the pressure of colonial regimes and the Japanese occupation. The analysis results show: (1) Denotatively and connotatively, Hamka's leadership is represented through the utilization of the Pedoman Masyarakat magazine as an instrument of "communication technology" and mass broadcasting to consolidate the organizational network across regions; (2) Hamka's da'wah authority is depicted as capable of mediating political tensions through elegant rhetoric and strategic lobbying; (3) The myth reproduced in this film asserts that the leadership of the ulama integrates media literacy proficiency with political communication flexibility. This article argues that Hamka's leadership model is an ideal prototype for Islamic organizational communication that is adaptive to media technology and the political constellations of its era.